A novel smart product-service system configuration method for mass personalization based on knowledge graph. (1st January 2023) - Dong, Liang; Ren, Mengyang; Xiang, Zhongxia; Zheng, Pai; Cong, Jingchen; Chen, Chun-Hsien
Abstract: Nowadays, manufacturing enterprises are struggling to satisfy personalized and dynamic user requirements. Smart Product-service System (Smart PSS), as a promising and sustainable business model, can respond to personalized and dynamic demands through effective configuration/reconfiguration processes. Mass personalization (MP), which emphasizes diversified values to improve user experience by considering both functional and affective elements, can significantly contribute to Smart PSS. However, Smart PSS field still lacks a unified knowledge representation framework and an effective configuration method in the MP context. Aiming to fulfill the gap, this research proposes a novel Smart PSS configuration method oriented to MP to meet personalized and dynamic requirements of users, especially satisfy affective and functional requirements simultaneously throughout the reconfiguration life-cycle. Due to the extreme complexity of heterogeneous data from Smart PSS and MP, Knowledge Graph (KG) is introduced as a powerful tool for managing intricate system knowledge. The common schemas of three KGs are constructed as the basis of configuration, with design knowledge, related field knowledge, and user information integrated comprehensively. KG-based question answering is combined with similarity calculation as a hybrid method in the configuration process to provide satisfactory and complete solutions. Moreover, the configuration process is placed in the reconfiguration life-cycle of Smart PSS to deal with dynamic changes through the latest knowledge in updating KGs. Furthermore, an illustrative case study of the intelligent management system for family medication is demonstrated. Through the comparison with other approaches, the proposed method is proved to be valuable for the implementation of Smart PSS configuration for MP.